Ejes estratégicos de la seguridad hemisférica en los gobiernos de George W. Bush y Barack Obama - Ayerbe, Luis Fernando [UNESP] (2010)
The paper approaches the U.S. perceptions about the sources of insecurity from Latin America, considered a low risk area and priority of its foreign policy. El análisis se concentra en la evaluación de las amenazas y desafíos a sus intereses estratégicos y las modalidades de actuación privilegiadas en la esfera regional, en que se verifican coincidencias entre las administraciones Demócratas y Republicanas en la adopción de un liderazgo con prerrogativas clasificatorias sobre los tipos de régimen político, con una agenda concebida como promoción de la convergencia hemisférica de democracias y economías liberales. The analysis focuses on assessing the threats and challenges to its strategic interests and privileged modes of action at the regional level, which verifies similarities between Republican and Democratic administrations in taking a leadership prerogatives qualifiers on the types political regime, with an agenda designed as promoting hemispheric convergence of liberal democracies and economies. En ese contexto, cabe destacar la prioridad atribuida a los países de la Alternativa Bolivariana para las Américas (ALBA) como eje opositor de sus políticas. In this context, include the priority given to the countries of the Bolivarian Alternative for the Americas (ALBA) as the linchpin of his political opponent.